Residents’ perceptions of urban densification and health – a systems dynamics approach - Lisa S. Barsties; Annemarie Ruijsbroek; Mariëlle A. Beenackers; Guus Luijben; Saskia W. van den Berg (BMC Public Health)
Abstract Background Little is known about residents’ perceptions of urban densification and its impact on health. A participatory systems dynamics approach can help to understand residents’ perspective on the complex system of interacting factors underlying urban densification and health. Methods We organised group model building sessions with three groups of residents that are living in Katendrecht, a highly densifying neighbourhood in the city of Rotterdam. The groups differed by length of residence (0–5, 10–15, and > 15 years). During the sessions, in which in total 25 residents participated, factors that influence health in the context of urban densification were identified and connected in causal loop diagrams. Also, possible actions to favourably adapt the system were discussed. Results According to the participants, densification of Katendrecht increased its attractiveness but negatively affected local social cohesion, the availability and diversity of facilities, and the accessibility of the area. The participants also did not feel sufficiently involved by local authorities in the development of the neighbourhood and argued that densification affects their mental health by increasing levels of stress and loneliness and decreasing enjoyment in living. The residents mainly mentioned actions that increase social cohesion and residential involvement in the neighbourhood’s development to maintain or improve their health in the context of densification. Conclusion This study illustrated the system underlying densification and residential health as a complex interaction between social and physical factors at the individual and neighbourhood level. Taking the perspective of residents into account can help to optimize future policies and urban densification plans in such a way that they do not harm and possibly even benefit residents’ health.